2020
DOI: 10.1073/pnas.1918809117
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a rabies virus polymerase complex from electron cryo-microscopy

Abstract: Nonsegmented negative-stranded (NNS) RNA viruses, among them the virus that causes rabies (RABV), include many deadly human pathogens. The large polymerase (L) proteins of NNS RNA viruses carry all of the enzymatic functions required for viral messenger RNA (mRNA) transcription and replication: RNA polymerization, mRNA capping, and cap methylation. We describe here a complete structure of RABV L bound with its phosphoprotein cofactor (P), determined by electron cryo-microscopy at 3.3 Å resolution. The complex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 46 publications
0
51
1
2
Order By: Relevance
“…In an NSV genome that encodes more than one viral protein, the promotor for transcription is located at the internal gene junction. The structure of the L-P complexes [55,[84][85][86] showed that the L protein is stabilized in the conformation prior to initiation by the bound P protein. The nascent RNA may exit to activate the capping and methyltransferase so that the elongation of mRNA will proceed [87].…”
Section: Viral Rna Synthesismentioning
confidence: 99%
“…In an NSV genome that encodes more than one viral protein, the promotor for transcription is located at the internal gene junction. The structure of the L-P complexes [55,[84][85][86] showed that the L protein is stabilized in the conformation prior to initiation by the bound P protein. The nascent RNA may exit to activate the capping and methyltransferase so that the elongation of mRNA will proceed [87].…”
Section: Viral Rna Synthesismentioning
confidence: 99%
“…It can be divided into four domains. These are the N-terminal domain (P NTD, aa 1-90, RABV), which is disordered but adopts defined conformations upon interaction with N or L [37][38][39][40][41][42]; the central domain (P CED, aa 91-130, RABV); the C-terminal intrinsically disordered domain (P CID, aa 131-195, RABV); and the C-terminal domain (P CD, aa 195-296, RABV). The atomic structures of P CED (pdb: 2fqm [43], VSV; pdb: 3l32 [44], RABV), which mediates the dimerisation of the P-protein, and P CD (pdb: 2k47 [45], VSV; pdb: 1vyi [46], RABV), which is important for interacting with the N-RNA complex and parts of the VSV P NTD with N [37], have been resolved.…”
Section: P-protein Structure and Functionmentioning
confidence: 99%
“…The P-protein is also the essential but catalytically inactive cofactor of L-protein. P NTD is the domain involved in the interaction with the L-protein [40,41,60,61]. This interaction is not essential for the enzymatic function of the L-protein, but rather for the generation of longer RNA molecules [62].…”
Section: P-protein Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations